2018
DOI: 10.1016/j.acap.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes Regarding Category B ACIP Recommendations Among Primary Care Providers for Children

Abstract: For category B recommendations to be useful in guiding practice, primary care clinicians will need to have a better understanding of their meaning, their implications for insurance payment, and guidance on how to discuss them with parents and patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 9 publications
3
26
1
Order By: Relevance
“…In another study, Kempe and colleagues reported that 56% and 38% of pediatricians and family physicians surveyed, respectively, were able to correctly define the category B recommendation. 26 One reason that these percentages were higher than those reported here may be the difference in how the survey questions were worded. The Kempe study asked respondents to define the recommendation, whereas our study asked HCPs to indicate how they decide whether to prescribe the MenB vaccine in their practice based on ACIP recommendations.…”
Section: Almost Always U S U a L L Ycontrasting
confidence: 62%
“…In another study, Kempe and colleagues reported that 56% and 38% of pediatricians and family physicians surveyed, respectively, were able to correctly define the category B recommendation. 26 One reason that these percentages were higher than those reported here may be the difference in how the survey questions were worded. The Kempe study asked respondents to define the recommendation, whereas our study asked HCPs to indicate how they decide whether to prescribe the MenB vaccine in their practice based on ACIP recommendations.…”
Section: Almost Always U S U a L L Ycontrasting
confidence: 62%
“…GRADE Category B is a recommendation for vaccination based on individual clinical decision‐making between the clinician and patient . Many physicians may misinterpret the individual decision‐making (previously Category B) recommendation to imply that they should decide whether or not to raise the topic with patients, while in reality the goal is for healthcare providers and patients to jointly discuss the benefits and risks of possible vaccination together to reach a clinical decision . In some cases, such as a lack of available information, ACIP may not make any recommendation…”
Section: Resultsmentioning
confidence: 99%
“…75 Many physicians may misinterpret the individual decision-making (previously Category B 76,77 ) recommendation to imply that they should decide whether or not to raise the topic with patients, while in reality the goal is for healthcare providers and patients to jointly discuss the benefits and risks of possible vaccination together to reach a clinical decision. 63,[78][79][80] In some cases, such as a lack of available information, ACIP may not make any recommendation. 75 In early 2015, ACIP issued a Category A recommendation for MenB vaccination of individuals ≥10 years of age at increased risk for IMD (Table 4 5 18 years.…”
Section: Grade Category a Indicates A Recommendationmentioning
confidence: 99%
“…57 Parents expect their children's physicians to provide guidance on adolescent vaccinations, 58 but studies have shown that these physicians struggle to understand the reasons for different types of meningococcal vaccines and the ACIP meningococcal vaccine recommendations. 59 For MenB vaccines, the ACIP Category B recommendation requires individual clinical decision-making in the context of a patientprovider discussion, 60 and several studies have shown that this recommendation is especially confusing for health-care providers to implement. 59,[61][62][63] However, it is noteworthy that the American Academy of Pediatrics states that not discussing MenB disease and the available licensed vaccines with families is not an option.…”
Section: Mo 1-2 Momentioning
confidence: 99%
“…59 For MenB vaccines, the ACIP Category B recommendation requires individual clinical decision-making in the context of a patientprovider discussion, 60 and several studies have shown that this recommendation is especially confusing for health-care providers to implement. 59,[61][62][63] However, it is noteworthy that the American Academy of Pediatrics states that not discussing MenB disease and the available licensed vaccines with families is not an option. 60 Taken together, these factors likely contribute to the disparate immunization rates for adolescent vaccines.…”
Section: Mo 1-2 Momentioning
confidence: 99%